Hypertension prevalence among indigenous populations in Brazil: a systematic review with meta-analysis - Zilmar Augusto de Souza Filho; Alaidistânia Aparecida Ferreira; Bernardo dos Santos; Angela Maria Geraldo Pierin (SciELO, 2015)
Abstract OBJECTIVE Evaluating the evidence of hypertension prevalence among indigenous populations in Brazil through a systematic review and meta-analysis. METHODS A search was performed by two reviewers, with no restriction of date or language in the databases of PubMed, LILACS, SciELO, Virtual Health Library and Capes Journal Portal. Also, a meta-regression model was designed in which the last collection year of each study was used as a moderating variable. RESULTS 23 articles were included in the review. No hypertension was found in indigenous populations in 10 studies, and its prevalence was increasing and varied, reaching levels of up to 29.7%. Combined hypertension prevalence in Indigenous from the period of 1970 to 2014 was 6.2% (95% CI, 3.1% - 10.3%). In the regression, the value of the odds ratio was 1.12 (95% CI, 1.07 - 1.18; p <0.0001), indicating a 12% increase every year in the probability of an indigenous person presenting hypertension. CONCLUSION There has been a constant increase in prevalence despite the absence of hypertension in about half of the studies, probably due to changes in cultural, economic and lifestyle habits, resulting from indigenous interaction with non-indigenous society.